2016
DOI: 10.1002/2015wr017601
|View full text |Cite
|
Sign up to set email alerts
|

Channel morphology and flow structure of an abandoned channel under varying stages

Abstract: Abandoned channels are those channels left behind as meandering rivers migrate over their floodplains and remain among the most enigmatic features of the riverscape, especially related to their hydraulics and geomorphology. Abandoned channels are being considered and implemented as restoration and rehabilitation strategies for large rivers but we do not yet have a sound understanding of their hydromorphodynamics. The overall objectives of this work were to assess the bed morphology and flow structure of a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…A considerable amount of work has been done on meandering river cutoffs, ranging from the long-term behaviour and organization of meandering rivers (Stolum, 1996(Stolum, , 1998Hooke, 2004;Camporeale et al, 2005Camporeale et al, , 2008Constantine and Dunne, 2008;Micheli and Larsen, 2011), mechanisms of cutoff initiation (Ratzlaff, 1981;Gay et al, 1998;Constantine et al, 2010b;Grenfell et al, 2012Grenfell et al, , 2014, rates of infill and sedimentology of oxbow lakes and floodplain alluvial architecture (Petersen, 1963;Erskine et al, 1982;Bridge et al, 1986;Piégay et al, 2002;Brooks and Medioli, 2003;Wren et al, 2008;Citterio and Piégay, 2009;Toonen et al, 2012;Dieras et al, 2013;Ishii and Hori, 2016), cutoff types and distribution within meandering rivers (Lewis and Lewin, 1983), hydrodynamics of cutoffs and the abandoned channel (Constantine et al, 2010a;Le Coz et al, 2010;Zinger et al, 2013;Costigan and Gerken, 2016;Richards et al, 2018), and morphologic changes following cutoff (Johnson and Paynter, 1967;Mosley, 1975;Gagliano and Howard, 1984;Hooke, 1995;Fares, 2000;Fuller et al, 2003;Han and Endreny, 2014). Based on the work mentioned above, several factors can be identified that provide first-order constraints on the morphologic evolution of meander cutoffs, namely (1) length of channel removed via...…”
Section: Introductionmentioning
confidence: 99%
“…A considerable amount of work has been done on meandering river cutoffs, ranging from the long-term behaviour and organization of meandering rivers (Stolum, 1996(Stolum, , 1998Hooke, 2004;Camporeale et al, 2005Camporeale et al, , 2008Constantine and Dunne, 2008;Micheli and Larsen, 2011), mechanisms of cutoff initiation (Ratzlaff, 1981;Gay et al, 1998;Constantine et al, 2010b;Grenfell et al, 2012Grenfell et al, , 2014, rates of infill and sedimentology of oxbow lakes and floodplain alluvial architecture (Petersen, 1963;Erskine et al, 1982;Bridge et al, 1986;Piégay et al, 2002;Brooks and Medioli, 2003;Wren et al, 2008;Citterio and Piégay, 2009;Toonen et al, 2012;Dieras et al, 2013;Ishii and Hori, 2016), cutoff types and distribution within meandering rivers (Lewis and Lewin, 1983), hydrodynamics of cutoffs and the abandoned channel (Constantine et al, 2010a;Le Coz et al, 2010;Zinger et al, 2013;Costigan and Gerken, 2016;Richards et al, 2018), and morphologic changes following cutoff (Johnson and Paynter, 1967;Mosley, 1975;Gagliano and Howard, 1984;Hooke, 1995;Fares, 2000;Fuller et al, 2003;Han and Endreny, 2014). Based on the work mentioned above, several factors can be identified that provide first-order constraints on the morphologic evolution of meander cutoffs, namely (1) length of channel removed via...…”
Section: Introductionmentioning
confidence: 99%
“…Meandering channels are omnipresent features of the Quaternary fluvial system. Abandoned channels are distinct meandering sub-environments that result from complex channel migration over the floodplain (Shen et al 2021); they develop through consecutive processes of cutoff initiation, plug bar formation, and channel disconnection (Costigan and Gerken 2016;Sedláček et al 2019;Ielpi et al 2021). Therefore, understanding abandoned channels' sedimentary processes can contribute significantly to understanding Quaternary fluvial systems.…”
Section: Introductionmentioning
confidence: 99%